The influence of sequence of alongside displacement of soil on stresses in buried pipeline in zone of mine subsidence - Yaskovets, Z. S.; Orynyak, I. V. (Mechanics and Advanced Technologies, 2018)
The paper deals with stress-strain state calculation of buried pipelines in the areas of coal mining. The effective algorithm for axial strain and displacement calculation based on notions of basic and correction solution was developed. The basic solution is algebraically corrected after each iteration step for correction solution, which obtained by numerically efficient transfer matrix method. A numerical iterative procedure for taking into account of the history of longitudinal soil displacements during mining is developed. It was found that the ignoring of the history of longitudinal soil displacements can cause to a significant underestimation of the stress state of the pipeline.